Determinants of the AUD/USD Exchange Rate and Policy Implications - Hsing, Yu (Asian Economic and Financial Review, 2015)
This paper examines short-run determinants of the Australian dollar/U.S. dollar (AUD/USD) exchange rate based on a simultaneous-equation model. Applying the EGARCH method, the paper finds that the AUD/USD exchange rate is positively associated with the 10-year U.S. real government bond yield, U.S. real GDP, the U.S. real stock price and the expected exchange rate and negatively influenced by the Australian real government bond yield, Australian real GDP, and the real Australian stock price.